THE NEW HORIZONS ABOUT CSR PARTNERSHIPS: A CASE STUDY OF CSR PARTNERSHIPS IN CILEGON, BANTEN - Ade Manggala Hardianto; Basuki Basuki; Bonnie Soherman (International Journal of Economy, Education and Entrepreneurship, 2022)
CSR partnership is a new horizon that involves stakeholders such as the local government of Cilegon city, companies, and non-governmental organizations. This study explores CSR partnerships to promote community welfare in Cilegon city. This research is qualitative by modifying action research to reflect CSR partnerships such as commitment and mission, initiative and awareness, vertical and horizontal relationships, proper behavior and fairness principles, and transparency. This research benefits by building a shared attitude (collaboration) and CSR partnership orientation to form actions